2012
DOI: 10.1073/pnas.1203559109
|View full text |Cite
|
Sign up to set email alerts
|

Impact of genetic dynamics and single-cell heterogeneity on development of nonstandard personalized medicine strategies for cancer

Abstract: Cancers are heterogeneous and genetically unstable. Current practice of personalized medicine tailors therapy to heterogeneity between cancers of the same organ type. However, it does not yet systematically address heterogeneity at the single-cell level within a single individual's cancer or the dynamic nature of cancer due to genetic and epigenetic change as well as transient functional changes. We have developed a mathematical model of personalized cancer therapy incorporating genetic evolutionary dynamics a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
135
0
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 102 publications
(140 citation statements)
references
References 38 publications
2
135
0
1
Order By: Relevance
“…Some studies used differential equation models formulated as deterministic optimal control problems (13)(14)(15)(16), whereas others used stochastic birth-death process models (17)(18)(19)(20)(21), to examine treatment regimens for tumors comprising a sensitive population along with a few resistant subpopulations. However, these studies, many of which dealt only with generic scenarios, focused primarily on drug scheduling, investigating the effects of frequency and dose intensity of drugs on resistance potential.…”
mentioning
confidence: 99%
“…Some studies used differential equation models formulated as deterministic optimal control problems (13)(14)(15)(16), whereas others used stochastic birth-death process models (17)(18)(19)(20)(21), to examine treatment regimens for tumors comprising a sensitive population along with a few resistant subpopulations. However, these studies, many of which dealt only with generic scenarios, focused primarily on drug scheduling, investigating the effects of frequency and dose intensity of drugs on resistance potential.…”
mentioning
confidence: 99%
“…91,92 Beckman et al . 93 illustrated that the potential effects on drug response and resistance acquisition induced by single cell heterogeneity and cellular dynamics can be mathematically modeled and, therefore, should be included in personalized treatment strategies. They demonstrated that a strategy targeting all cancer subpopulations including the precursors of resistant clones, rather than treatment targeting the clone predominantly present which therefore initially leads to the largest reduction in tumour size, may be more effective.…”
Section: Cancer Systems Biology Approachesmentioning
confidence: 99%
“…In the spirit of Beckman et al (39), who also investigated the impact of heterogeneity on different therapies, we assume that tumour growth is unbounded and that tumour heterogeneity is due to differential drug response among different subclones. This is of course a gross simplification, but allows us to focus on the relevant aspects of clonal evolution and the acquisition of resistance.…”
Section: Population Dynamicsmentioning
confidence: 99%